2003
DOI: 10.1021/ma0344902
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical α-Process in Polyethylene

Abstract: Introduction.Although the origin and the underlying mechanisms of the mechanical R-process in polyethylene have been extensively studied, [1][2][3][4][5][6][7][8] there is still no general agreement about the microscopic origin. Two points are mainly discussed: first, whether there are two R-processes (R I and R II in the order of increasing temperature) as often seen in measurements using dynamic mechanical analysis (DMA) 5,7-15 or whether there is only one high-temperature process as observed in nuclear magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
67
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 35 publications
(55 reference statements)
0
67
0
1
Order By: Relevance
“…The α 1 and α 2 relaxations were assigned as relaxation in the grain boundaries and the thermal activation of the intrachain motion, respectively. These assignments were confirmed by dynamic mechanical analysis (DMA) of PE single-crystal mats [5] and PE with different molecular weight distributions and branch structures [6]. Because molecular motion is activated in the α relaxation region, the drawability of polymeric materials is highly enhanced.…”
Section: Introductionmentioning
confidence: 76%
“…The α 1 and α 2 relaxations were assigned as relaxation in the grain boundaries and the thermal activation of the intrachain motion, respectively. These assignments were confirmed by dynamic mechanical analysis (DMA) of PE single-crystal mats [5] and PE with different molecular weight distributions and branch structures [6]. Because molecular motion is activated in the α relaxation region, the drawability of polymeric materials is highly enhanced.…”
Section: Introductionmentioning
confidence: 76%
“…and testing conditions (frequency of oscillations, heating rate, intensity of preloading, etc.). For recent DMTA (dynamic mechanical thermal analysis) observations on polyethylenes, see Matthews et al (1999), Kuwabara et al (2000), Mano (2001), Sirotkin and Brooks (2001), Matsuo et al (2003), Men et al (2003), Kolesov et al (2005), Stadler et al (2005), Na et al (2007), Guan and Phillips (2007), and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been suggested regarding molecular mechanisms of a-relaxation: c-shear within crystalline lamellae (homogeneous shear of crystal blocks in the direction of their c-axis) (Sirotkin and Brooks, 2001;Guan and Phillips, 2007), inter-lamellar shear (slip of crystalline blocks past each other) (Matthews et al, 1999;Jiang et al, 2009), sliding of tie molecules and motion of chain folds and loops through crystals (Khanna et al, 1985), diffusion of chains (Men et al, 2003) and defects (Alberola et al, 1990) in crystallites, growth of mobility of chains in the interphase (transition regions located in the close vicinity of lamellar surfaces) (Rastogi et al, 2007), weakening of lamellar coupling and enhancement of segment exchange between crystalline and amorphous phases (Kolesov et al, 2005;Na et al, 2007;Zubova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[25] and references therein), and the a 2 -peak (at higher temperatures) e to crystalline deformation. Only after the direct NMR observation of the flips of chains in crystallites [6], several authors began to associate one of the mechanically observed a-peaks (a 1 [27] or a 2 [26]) with the chain diffusion through crystallites and so to identify one of the mechanical processes with the dielectrically and NMR observed H-process. Kolesov et al [28] uses this idea of the chain diffusion for the qualitative explanation of the influence of crystal morphology and chain branching on parameters of the unresolved mechanical process.…”
Section: Introductionmentioning
confidence: 99%